Enhancing Emergency Management Skills Through Manikin-Based Basic Life Support Simulations: An Evidence-Based Approach for Nursing Students - Husain, Fida; Silvitasari, Ika; Hermawati, Hermawati; Inovasi, Monica (Inspirasi Foundation, 2024)
Introduction: Effective Basic Life Support (BLS) is crucial in improving survival rates during emergencies. Current nursing education often relies on traditional methods, which may not fully prepare students for the pressure and decision-making required in real-life situations. Objective: This study explores the effectiveness of manikin-based BLS simulation with scenarios in enhancing nursing students' skills in emergency management. Method: This study employed a one-group pre-test post-test design. Thirty nursing students were randomly assigned to participate in a Manikin-Based BLS Simulation training program. Their BLS skills were assessed using a validated and reliable questionnaire based on the American Heart Association (AHA) 2020 guidelines, administered both before and after the training. Data collection occurred in May 2024. The subsequent analysis will compare pre-test and post-test scores to evaluate the effectiveness of the Manikin-Based BLS Simulation in improving students' BLS skills. Result: Post-training, knowledge improved significantly (p < 0.001), with 93.3% of students achieving 'Good' knowledge and 96.7% passing skill assessments. Conclusion: Manikin-based simulations effectively enhance knowledge and skills, supporting their integration into nursing curricula.